Impacts of Retail and Export Demand on United States Cattle Producers. Issue 3 (26th August 2019) - McKendree, Melissa G. S.; Tonsor, Glynn T.; Schroeder, Ted C.; Hendricks, Nathan P.
Abstract : Despite its importance in many decisions throughout agriculture, limited empirical work has quantified how changes in primary demand impact producers operating at different levels of vertically‐connected industries. A structural system of equations was estimated to quantify the impacts of U.S. retail and export beef demand on fed and feeder cattle demand and supply. Increases in retail and export demand positively impact both feeder and fed cattle producers. The estimated transmission elasticities suggest that shifts in retail and export demand, whether positive or negative, accrue proportionally more to feeder cattle producers than fed cattle producers. Using estimates from previous literature of the effect of generic advertising on beef demand, simulation results suggest feeder and fed cattle producers would benefit from increasing beef checkoff assessments from $1 to $2. Furthermore, an increase in export demand of more than 3.5% from observed values would cover aggregate costs of implementing source and age verification. While primary suppliers are often not directly involved in primary demand activities in vertically‐connected industries, this study highlights the key economic value for primary suppliers to support demand enhancing activities.